Problem Solving Ability According to Polya on System of Linear Equations in Two Variables Based on Student Learning Styles - Budi Murtiyasa; Shinta Wulandari (Didaktik Matematika, 2022)
The ability to solve mathematical problems can be said to be still low. Learning style is one of the factors that affect it. The purpose of the research conducted is to describe mathematical problem-solving skills based on learning styles. This research uses a type of research in the form of qualitative descriptive research. The subjects used were 3 students of class VIII with each having a different learning style. The selection of subjects for as many as three students in this study was on purposive sampling. This study used instruments in the form of questionnaires, tests, and interviews. The techniques used when analyzing data are to carry out the stages of data reduction, data presentation, and drawing conclusions. Checking the validity of the data using triangulation techniques. Troubleshooting using Polya steps. This study shows several results as follows: (1) subjects who have a visual learning style are able to understand problems, devise a plan, carry out the plan, and looking back, (2) subjects who have an auditory learning style are able to understand problems, devise a plan, carry out the plan, and looking back, and (3) subjects who have a kinesthetic learning style do not understand the problem, devise a plan, carry out the plans, and do not looking back.